Strategi Meningkatkan Motorik Kasar melalui Pembelajaran Senam Kebugaran Jasmani 2018 Pada Siswa Kelas 5 dan 6 Sekolah Dasar Negeri Kletekan 2 - Insani, Annisa Mutiara; Jariono, Gatot; Syaukani, Agam Akhmad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to improve students' gross motor skills through the 2018 Physical Fitness Gymnastics (SKJ) program for 5th and 6th graders at Kletekan 2 Elementary School. The research uses Classroom Action Research (CAR) with two cycles that include planning, implementation, observation, and reflection. Results show that in the first cycle, student mastery reached only 68%, while in the second cycle it increased to 80%, indicating the achievement of the target. In conclusion, implementing SKJ 2018 effectively enhances students' gross motor skills and can serve as a sustainable method for physical education in schools. Keywords: elementary students, gross motor skills, gymnastics, physical education, SKJ 2018